2010
DOI: 10.1021/jf903203n
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Content, Radical Scavenging Properties, and Essential Oil Composition ofOriganumSpecies from Different Populations

Abstract: The aim of this work was to compare the antiradical activity, total phenol content (TPC), and essential oil composition of Origanum vulgare spp. virens, Origanum x applii, Origanum x majoricum, and O. vulgare spp. vulgare cultivated in Argentina in different localities. The experiment was conducted in the research station of La Consulta (INTA-Mendoza), the research station of Santa Lucia (INTA-San Juan), and Agronomy Faculty of National University of La Pampa, from 2007 to 2008. The composition of the essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 25 publications
8
74
0
5
Order By: Relevance
“…Vulgare y Virens (OVV) han sido mencionadas por ser ricas en compuestos sesquiterpenoides (germacrene D), y monoterpenos (terpinen-4-ol) (Sezik, Tumen, Kirimer, Ozek y Baser, 1993;Kula, Majda, Stoyanova y Georgiev, 2007;Dambolena et al, 2010); sin embargo, los quimiotipos frecuentemente determinados son carvacrol y timol. Los factores principales y secundarios, como la herencia genética, edad de las plantas y elementos ambientales, influyen en sus concentraciones dentro de una misma especia (Poulose y Croteau, 1978).…”
Section: Análisis Cromatográfico (Gc-ms) Del Aceite Esencial De Oréganounclassified
“…Vulgare y Virens (OVV) han sido mencionadas por ser ricas en compuestos sesquiterpenoides (germacrene D), y monoterpenos (terpinen-4-ol) (Sezik, Tumen, Kirimer, Ozek y Baser, 1993;Kula, Majda, Stoyanova y Georgiev, 2007;Dambolena et al, 2010); sin embargo, los quimiotipos frecuentemente determinados son carvacrol y timol. Los factores principales y secundarios, como la herencia genética, edad de las plantas y elementos ambientales, influyen en sus concentraciones dentro de una misma especia (Poulose y Croteau, 1978).…”
Section: Análisis Cromatográfico (Gc-ms) Del Aceite Esencial De Oréganounclassified
“…Phenol content was measured at 760 nm using a spectrophotometer (Hewlett Packard HP 8452 A, Palo Alto, CA, USA). Phenol content was expressed as mg/g (Dambolena et al, 2010).…”
Section: Free-radical Scavening Activity (Frsa) and Total Phenolic Comentioning
confidence: 99%
“…Others compounds have presented different tendency (Ahmad et al 2010;Faizal et al 2011;Hayta et al 2011;Mohanty et al 2011;Shaik et al 2011). Dambolena et al (2010), who reported studies of several Argentinian oregano species, concluded that there was not evidence that total phenolics content is affected by environmental factors. Nonetheless, in this study we observed that in vitro conditions affected TP and ORAC increasing its contents and activities probably by factors related to in vitro conditions such as high humidity, water and light stress.…”
Section: Luteolin Contentmentioning
confidence: 99%